Design, synthesis and biological evaluation of paralleled Aza resveratrol–chalcone compounds as potential anti-inflammatory agents for the treatment of acute lung injury. Issue 15 (1st August 2015) - Chen, Wenbo; Ge, Xiangting; Xu, Fengli; Zhang, Yali; Liu, Zhiguo; Pan, Jialing; Song, Jiao; Dai, Yuanrong; Zhou, Jianmin; Feng, Jianpeng; Liang, Guang
Graphical abstract Paralleled Aza resveratrol–chalcone compounds were synthesized and evaluated for anti-inflammatory activities in the treatment of ALI.